Samadhining Anglayarakěn Anak Mitra: Antara Lautan dan Pegunungan - Abimardha Kurniawan (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2016)
This article describes a manuscript entitled Samadhining Anglayarakěn Anak Mitra (SAAM) that became a part of a compendium manuscript of National Library of Indonesia’s collection with call number L 109 peti 9. This Buda’s manuscript has been included as a part of a Merapi-Merbabu collection. This text also includes some text which came from two traditions that ever had a great influence in Java: Islamic and pre-Islamic traditions. SAAM is a unique text because it was written in the community who live far away from the sea even agrarian, but this text presents an overview about some religious activities related to maritime world. This indicates that the maritime life has affected the structure of their experiences. This article is a preliminary study using philology, codicology, and the interpretation of textual and cultural codes. Through that various approaches, this article explains several things, namely (1) the origin of the text and its materials; (2) the relationship between mountains and maritime religious communities; and (3) the understanding of the text producers community on the maritime world. — Artikel ini membahas naskah Samadhining Anglayarakěn Anak Mitra (SAAM) yang termuat dalam naskah compendium koleksi Perpustakaan Nasional Republik Indonesia dengan nomor koleksi L 109 peti 9. Naskah beraksara Buda tersebut termasuk dalam koleksi Merapi-Merbabu. Naskah ini juga memuat beberapa teks yang berasal dari dua tradisi yang memiliki pengaruh besar di Jawa: tradisi Islam dan pra-Islam. Teks SAAM cukup unik karena berada dalam lingkup komunitas yang tinggal jauh dari laut dan bercorak agraris, namun menyajikan gambaran aktivitas religus yang berkaitan dengan dunia perarian (bahari). Ini berarti bahwa kehidupan bahari telah masuk ke dalam struktur pengalaman mereka. Artikel ini merupakan kajian pendahuluan yang menggunakan pendekatan filologi, kodikologi, disertai upaya interpretasi kode-kode tekstual dan kultural. Melalui berbagai pendekatan itu, artikel ini menjelaskan beberapa hal, yaitu (1) seluk-beluk teks serta objek material yang memuatnya; (2) hubungan antara komunitas religius di pegunungan dengan dunia bahari; serta (3) pandangan komunitas produsen teks terhadap dunia bahari.